Disputes over the concept of ecological economics and environmental economics in the light of the works of Professor Tomasz çZylicz - Stanisław Czaja (Central European Economic Journal (CEEJ), 2021)
The problem of the concept of ecological and environmental economics and the relationship between them is the vital research problem in modern economics. The presentation of disputes in this respect is the subject of the presented article. For obvious, substantive and non-substantive reasons, the scientific views of Professor Tomasz çZylicz will be the central axis. The purpose of the topic presented in this paper analysis is not to settle the controversy but to present the dispute using the views of some discussion participants, especially the comments formulated by Professor Tomasz çZylicz. The research method is based on a critical analysis of the literature and desktop research. Conclusion 1: The problem of understanding ecological and environmental economics is just one of the many important issues that can be found in the works of Professor Tomasz çZylicz. Conclusion 2: This problem is connected with very interesting theoretical, cognitive and terminological issues and practical issues related to the implemented environmental policies or sustainable development strategies at their various levels.
Keywords: Q5; 330; ecological economics; environmental economics; modern economics